The contribution of social media to project management. Issue 4 (31st May 2019) - Kanagarajoo, Muralitheran V.; Fulford, Richard; Standing, Craig
Abstract : Purpose: The purpose of this paper is to determine the social media (SM) tools that are the most prevalent for project management activities, ascertain the areas of project management that are most benefited by SM, elucidate enablers and inhibitors to adoption of SM and identify the implications for virtual teams. Design/methodology/approach: A Delphi study was used to explore why and how SM is being utilized in projects. In total, 32 participants contributed to three rounds of Delphi study, comprising two rounds of questionnaire followed by confirmatory interviews. The vulnerabilities and difficulties associated with the use of SM were examined by qualitative interviews. Findings: Information sharing SM tools, such as YouTube, Dropbox, SlideShare, flickr, CrowdStorm and Instagram, are the most advantageous to project management. However, the tools utilized differ at different stages of the project lifecycle. The major benefit of SM is that it enables project teams to communicate efficiently and positively affects virtual team dynamics. Adoption can be inhibited by the absence of infrastructure in rural areas and differing preferences for SM tools in global regions. There is also a perceived lack of maturity of policies and procedures to govern SM adoption and use. Research limitations/implications: The research was conducted based on the Project Management Body of Knowledge version 5 project management processes. Practical implications: The findings will enable practitioners to select SM tools that are suitable for project activities and forewarn about potential shortfalls. The findings also facilitate a qualitative analysis of SM attributes and their effect on project management. Social implications: Project practitioners can use the findings to adopt SM for their project management. Originality/value: This study extends the literature concerning the use of SM for project management, provides a foundation for future research and may present as a useful guide for the adoption of relevant SM tools.